Inhibition of Human Sulfotransferases by Phthalate Monoesters - Huang, Hui; Lan, Bei-Di; Zhang, Yu-Jing; Fan, Xiao-Juan; Hu, Min-Cui; Qin, Guo-Qiang; Wang, Fei-Ge; Wu, Yue; Zheng, Tao; Liu, Jun-Hui (Frontiers in Endocrinology, 2022)
Objective: This study aimed to investigate the inhibition of human important phase II metabolic enzyme sulfotransferases (SULTs) by phthalate monoesters which are important metabolites of phthalate esters (PAEs). Method: Recombinant SULTs-catalyzed metabolism of p-nitrophenol (PNP) was employed as the probe reactions of SULTs to investigate the inhibition of 8 kinds of phthalate monoesters towards SULTs isoforms. In vitro incubation system was utilized for preliminary screening, and 100 μM of phthalate monoesters were used. Inhibition kinetics were carried out to determine the inhibition of SULTs by phthalate monoesters. Result: Multiple phthalate monoesters have been demonstrated to exert strong inhibition potential towards SULT1A1, SULT1B1 and SULT1E1, and no significant inhibition of phthalate monoesters towards SULT1A3 was found. The activity of SULT1A1 was strongly inhibited by mono-hexyl phthalate (MHP), mono-octyl phthalate (MOP), mono-benzyl phthalate (MBZP) and mono-ethylhexyl phthalate (MEHP). Monobutyl Phthalate (MBP), MHP, MOP, mono-cyclohexyl phthalate (MCHP) and MEHP significantly inhibited the activity of SULT1B1. MHP, MOP, and MEHP significantly inhibited the activity of SULT1E1. MOP was chosen as the representative phthalate monoesters to determine the inhibition kinetic parameters (Ki) towards SULT1B1 and SULT1E1. The inhibition kinetic parameters (Ki) were calculated to be 2.23 μM for MOP-SULT1B1, and 5.54 μM for MOP-SULT1E1. In silico docking method was utilized to understand the inhibition mechanism of SULT1B1 by phthalate monoesters. Conclusions: All these information will be beneficial for understanding the risk of phthalate monoesters exposure from a new perspective.